Catalytic performance of a boron peroxotungstate complex under homogeneous and heterogeneous conditions - Santos, Isabel C. M. S.
The preparation and characterization (FT-IR, FT-Raman, B-11 MAS NMR, diffuse reflectance, elemental analysis) of a novel boron peroxotungstate (BTBA)(4)H[BW4O24] (BTBA = benzyltributylammonium) is reported, along with its use in the homogeneous oxidation of cis-cyclooctene, geraniol, linalool and (-)-carveol with H2O2 as oxidant and acetonitrile as solvent. High catalytic activity was registered for all the substrates studied under homogeneous conditions, namely 99% of conversion of geraniol after 2 h, 93% for linalool after 5 h, 74% for cis-cyclooctene after 6 h, and 100% for (-)-carveol after 2 h of reaction. Some oxidation studies were carried out with the Venturello complex, [PW4O24](3-), in the same conditions. Furthermore, the boron peroxotungstate (BW4) was immobilized using two different strategies: (a) BW4 anchored into a functionalized silica (aptesSiO(2)) giving BW4@aptesSiO(2) and (b) BW4 encapsulated on a metal organic framework, commonly referred as MIL-101, giving BW4@MIL-101. The catalytic activity of both heterogeneous materials was investigated for geraniol oxidation and the results were compared with those obtained with BW4 under homogeneous conditions. The encapsulated boron peroxotungstate (BW4@MIL-101) gave rise to the best results, reaching complete conversion of geraniol after 3 h of reaction and 78% selectivity for 2,3-epoxygeraniol. Additionally, this heterogeneous catalyst could be reused without appreciable loss of catalytic activity, affording similar 2,3-epoxygeraniol selectivity. The heterogeneous catalysts' stability was also investigated after the oxidation reactions by different characterization techniques. (C) 2012 Elsevier B. V. All rights reserved.